Oil and Gas Fiscal Term Regulations Based on Ecological Justice - Manumayoso, Bambang; Annissa Dewi Rinenggo Kusumo Utami; Luiza Gabunia (Lembaga Contrarius Indonesia, 2024)
This study aims to analyze the National Fiscal-Term of Oil and Natural Gas Producer Sharing Contract (PSC) Cost Recovery and Gross Split models that are not in accordance with the principles of ecological justice. This study employs doctrinal legal approach. State control over natural resources in the Indonesian constitution emphasizes state authority to manage these resources for the prosperity of the people, reflected in various legal frameworks, including regulations regarding the PSC model used in the oil and gas sector. The results of the study show that oil and gas management in Indonesia follows Article 33 of the 1945 Constitution, with two central schemes of PSC Cost Recovery and Gross Split. This regulation ensures fair, efficient, and sustainable oil and gas management. Different countries implement diverse regulations for oil and gas exploration and production, including variations in tax periods and tariffs. In Indonesia, the exploration period is set at six years, with production rights extending up to thirty years. This contrasts with the regulations in other countries, such as China and India. To ensure that environmental impacts are duly considered and that local communities are engaged, oil and gas management in Indonesia should be guided by principles of ecological justice rooted in Pancasila. Challenges such as inadequate data, policy inconsistencies, and limited oversight capacity must be addressed through enhanced transparency and policy harmonization.